Digital literacies and children's personalized books: Locating the 'self' (UCL Press, 2020)
This conceptual article discusses the role of digital literacies in personalized books, in relation to children's developing sense of self, and in terms of assessing the potential impact of artificial intelligence (AI). Personalized books contain children's data, such as their name, gender or image, and they can be created by readers or automatically by the publisher. Some personalized books are e-books enhanced with artificial intelligence, and some can be ordered as paperbacks. We discuss this use of children's personal data in terms of the social location of the self with regard to subjective and objective dimensions. We draw on a map metaphor, in which objective space requires readers to locate themselves in an unknown 'A-to-B' space and subjective space provides an individually oriented world of 'me-to-B'. By drawing on examples of personalized books and their use by parents and young children, we discuss how personalization troubles the borders between readers' me-to-B and A-to-B space experiences, leading to possible confusion in the sense of self. We conclude by noting that AI-enhanced personalized texts can reduce personal agency with respect to formulating a sense of identity as a child.